Estimates of the global, regional, and national burden of atrial fibrillation in older adults from 1990 to 2019: insights from the Global Burden of Disease study 2019 - Jiao, Min; Liu, Chenglin; Liu, Yongwen; Wang, Yan; Gao, Qianqian; Ma, Anning (Frontiers in Public Health, 2023)
Background Atrial fibrill ation (AF) is a predominant public health concern in older adults. Therefore, this study aimed to explore the global, regional, and national burden of AF in older adults aged 60–89 between 1990 and 2019. Methods The morbidity, mortality, disability-adjusted life years (DALYs), and age-standardized rates of AF were refined from the Global Burden of Diseases study 2019. The epidemiological characteristics were assessed based on numerical values, age-standardized rates per 100,000 person-years, and estimated annual percentage changes (EAPC). Results Globally, a total of 33.31 million AF cases, 219.4 thousand deaths, and 65.80 million DALYs were documented in 2019. There were no appreciable changes in EAPC from 1990 to 2019. The disease burden of AF differed significantly across different territories and countries. At the national level, China exhibited the highest number of incident cases [818,493 (562,871–1,128,695)], deaths [39,970 (33,722–46,387)], and DALYs [1,383,674 (1,047,540–1,802,516)]. At the global level, high body mass index (BMI) and high systolic blood pressure (SBP) were two predominant risk factors contributing to the proportion of AF-related deaths. Conclusion AF in older adults remains a major public health concern worldwide. The burden of AF varies widely at both national and regional levels. From 1990 to 2019, the cases of incidences, deaths, and DALYs have shown a global increase. The ASIR, ASMR, and ASDR have declined in the high-moderate and high SDI regions; however, the burden of AF increased promptly in the lower SDI regions. Special attention should be paid to the main risk factors for high-risk individuals with AF, which can help control systolic blood pressure and body mass index within normal limits. Over all, it is necessary to illustrate the features of the global AF burden and develop more effective and targeted prevention and treatment strategies.